Microstructure of injection moulding machine mould clamping mechanism: design and motion simulation. Issue 3 (13th May 2019) - Jin, Zhiming; Zhang, Yajun; Wang, Xinliang; Williams, Jacob; Liu, Zhen; Huang, Zhongyuan; Falkner, D'Lauren; Zhou, Gang; Dong, Liqun; Zhuang, Jian; Wang, Zhe
Abstract : With the advent of intelligence technologies, more and more machines and devices are involved in the creation of complex structures. In the intelligent manufacturing industries, mouldings including injection moulding, blow moulding, compression moulding, and others play critical roles in manufacturing highly precise parts required for building intelligent machines (such as computers, cell phones, robots etc.). The performance of the clamping mechanism directly affects the quality of the microstructure of injection products. The design of the injection moulding mould clamping mechanism is based on the microstructure characteristics of the trip of the toggle lever mechanism ratio, speed ratio, and force amplification ratio. These are used to study the main performance parameters, such as analysis, as well as for the establishment of the physical model of the clamping mechanism. The model is based on the microstructure of injection of hyperbolic elbow clamping mechanism kinematics simulation. Simulation results and theoretical calculation contrast analysis show that the maximum dynamic template speed is 215.34 mm/s. The dynamic templates and cross‐head speed ratio is 2.15; therefore, the design of the injection moulding mould clamping mechanism for the microstructure provides favourable technical support. The method described here is important to build complicated moulds required to build highly precise parts to build intelligent machineries.